A checklist of stag beetles (Coleoptera: Scarabaeoidea: Lucanidae) from Iran - Bartolozzi, Luca; Ghahari, Hassan; Sprecher-Uebersax, Eva; Zilioli, Michele (Zootaxa, 2014)
An updated checklist of the Lucanidae (Coleoptera) from Iran is given. New locality records are listed and some dubious distributional records are discussed. Dorcus vavrai Nonfried, 1905 is placed in synonymy with Dorcus peyronis Reiche and Saulcy, 1856 (new synonymy) The female of Lucanus xerxes Král, 2004 is described. A key for the identification of the Iranian stag beetle species is also provided and all the species are figured.